Indonesian Language Learning Using the Discovery Learning Model Based on High Order Thinking Skills (HOTS) on Students' Analytical Thinking Ability - Cecep Wahyu Hoerudin (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Along with the rapid development of the world, requires students to become individuals who are increasingly analytical of problems. Discovery learning is a student-centered learning model and an active learning experience. In the process, this learning model will make students actively discover and express their ideas related to the topic being studied. This research aimed to examine the impact of discovery learning model based on higher-order thinking skills (HOTS) on students analytical thinking skills in learning Indonesian. The research was a quantitative approach and experiment method (quasi-experiment research), uses post-test control and experiment group design. The population in this research was the students of class X Islamic Senior High School (MAN) 1 Malang East Java, Indonesia. The sampling was taken using the cluster random sampling technique. The instrument used to collect data was a test balance. It was analyzed using SPPS with the independent sample t-test formula. The results of this research are: the significance value of variable analysis is 0.00 <0.05.  It means there is an impact of the discovery learning model based on higher-order thinking skills (HOTS) on students' analytical skills. Implicitly, it can improve students' abilities in understanding the material, therefore the students can think analytically when they find problems in learning.